1959
DOI: 10.1111/j.1423-0410.1959.tb03628.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on the A, B, O(H) Blood Substances in the Saliva and the Milk

Abstract: Ahrgnnli, C.; Creaasri. A.; Sewn, A.; Beolchini, P . E.; Borbaini. S. and Ginnotri, G. A,:Vox Sang. 4: 261-211 (1959)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

1962
1962
1981
1981

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 4 publications
1
4
1
Order By: Relevance
“…The average titer of the H substance in O persons is higher in milk. This finding confirms the results of Morganti et al [6] but not those of Denborough et al [3] who found higher H scores in saliva. An analysis of variance considering the PI average sali vary titers of individuals with different ABO blood groups indicated that the differences were statistically significant (F4>20-= 29.8; p < 0.001).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The average titer of the H substance in O persons is higher in milk. This finding confirms the results of Morganti et al [6] but not those of Denborough et al [3] who found higher H scores in saliva. An analysis of variance considering the PI average sali vary titers of individuals with different ABO blood groups indicated that the differences were statistically significant (F4>20-= 29.8; p < 0.001).…”
Section: Resultssupporting
confidence: 83%
“…In a general way the titers we obtained in this last fluid are higher than those observed by other authors [3,5,6]; this can be ex plained by differences in the time that elapsed between delivery and sample collec tion. In our study this was standardized (2 days) while in these three other investiga tions the material was obtained at variable periods, after the third day.…”
Section: Resultscontrasting
confidence: 52%
See 2 more Smart Citations
“…Compared with saliva, human milk from group A and B secretors contains more H activity than A or B [5]. Szulman [8] has suggested that this may be caused by competition for galactose which is necessary to form A and B antigen.…”
Section: Sda In Milkmentioning
confidence: 99%